The oncoprotein and stem cell renewal factor BMI1 associates with poor clinical outcome in oesophageal cancer patients undergoing preoperative chemoradiotherapy - Yoshikawa, Reigetsu (BioMed Central, 2012)
BACKGROUND: The polycomb group (PcG) family BMI1, acting downstream of the hedgehog (Hh) pathway, plays an essential role in the self-renewal of haematopoietic, neural, and intestinal stem cells, and is dysregulated in many types of cancer. Our recent report has demonstrated that Hh signalling activation can predict very earlier relapse of oesophageal cancers. As data were not available on the clinical role of BMI1 expression in oesophageal cancers after chemoradiotherapy (CRT), we analysed whether it could be also used to predict disease progression and prognosis in oesophageal cancer patients undergoing trimodality therapy of preoperative CRT and oesophagectomy. METHODS: Expressions of BMI1 and p16(INK4A), a downstream target of PcG, were analysed in 78 patients with histologically confirmed oesophageal squamous cell carcinoma (ESCC) after preoperative CRT by immunohistochemical staining. The association of BMI1 and p16(INK4A) expression with clinicopathologic characteristics was analysed by χ(2)-test. Survival analysis was carried out by the log-rank test using Kaplan-Meier method. RESULTS: Among 78 ESCC patients, 24 patients (30.8%) showed BMI1 positivity, mainly localised in the nuclei of tumour cells. Patients harbouring BMI1-positive tumour cells showed significantly poorer prognoses than those without such cells or residual tumours (mean disease-free survival (DFS) time 16.8 vs 71.2 months; 3-yr DFS 13.3% vs 49.9%, P=0.002; mean OS time 21.8 vs 76.6 months; 3-yr OS 16.2% vs 54.9%, P=0.0005). There was no significant correlation between p16(INK4A) expression and BMI1 expression. CONCLUSIONS: Our study shows that BMI1 expression is a predictor of early relapse and poor prognosis in ESCC after CRT. These findings suggest that BMI1 signal activation might be involved in promoting cancer regrowth and progression after CRT, and might be indicative of emergence of ‘more aggressive’ cancer progenitor cells.